2020
DOI: 10.37022/wjcmpr.2020.2214
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Anti Inflammatory Activity of Methanolic and Ethanolic Leaf Extract of Psidium Guajava

Abstract: The objective of the current research work was to determine the anti inflammatory activity of Psidium guajava by the Human Red Blood Cell membranes stabilization method. The methanol and ethanol leaf extract of plant Psidium guajava were investigated for their invitro anti-inflammatory property by Human red blood cell membrane stabilization method. The prevention of hypotonocity induced HRBC membrane lysis was taken as a measure of a anti-inflammatory activity. The anti inflammatory activity of methanol and et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…A study with a different method on membrane stabilization effect conducted by Hotta et al, the study reported that methanol and ethanol leaf extracts of Psidium guajava L. were found to have a membrane-stabilizing effect by inhibiting hypotonicity-induced erythrocyte membrane lysis, according to the report. The methanol leaf extract of Psidium guajava had the strongest anti-inflammatory function, while the ethanol leaf extract had the weakest 33 .…”
Section: Effect Of Psidium Guajava L On Lysosomal Membrane Stabilizationmentioning
confidence: 96%
“…A study with a different method on membrane stabilization effect conducted by Hotta et al, the study reported that methanol and ethanol leaf extracts of Psidium guajava L. were found to have a membrane-stabilizing effect by inhibiting hypotonicity-induced erythrocyte membrane lysis, according to the report. The methanol leaf extract of Psidium guajava had the strongest anti-inflammatory function, while the ethanol leaf extract had the weakest 33 .…”
Section: Effect Of Psidium Guajava L On Lysosomal Membrane Stabilizationmentioning
confidence: 96%